Incisional Hernia After Minimally Invasive Lateral Retroperitoneal Surgery: Case Series and Review of the Literature. Issue 3 (27th April 2018) - Vivas, Andrew C; Januszewski, Jacob; Hajirawala, Luv; Paluzzi, Jason M; Gandhi, Shashank V; Uribe, Juan S
Abstract: BACKGROUND: Minimally invasive lateral retroperitoneal (lateral-MIS) approaches to the spine involve traversing the lateral abdominal wall musculature and fascia. Incisional hernia is an uncommon approach-related complication. OBJECTIVE: To review the incidence, treatment, and preventative measures of incisional hernia after lateral-MIS approaches. METHODS: This is a retrospective review of cases performed by a single surgeon from 2011 to 2016. All patients who underwent lateral-MIS approaches at this institution were included. Patients with a postoperative diagnosis of lateral hernia on physical exam and corroborating advanced imaging findings were included in this study. Cases of flank bulge due to peripheral nerve injury were excluded. RESULTS: Three-hundred three patients underwent lateral-MIS approaches to the spine. Three (1%) patients with incisional hernia were identified. Two patients presented with a clinically symptomatic incisional hernia, while 1 patient was diagnosed incidentally after a routine abdominal magnetic resonance imaging for an unrelated reason. No patients suffered bowel entrapment or strangulation. CONCLUSION: Incisional hernia after lateral-MIS approaches is rare. Patients with incisional hernias may be susceptible to bowel incarceration and ischemia, though the incidence of this is probably low. Meticulous closure of the fascia is critical to avoiding this complication.